The Effect of Pictorial Riddle Assisted Inquiry Learning Model on Metacognition Awareness of Biology Students - Destia Putri Oktaviani; Suratno Suratno; Kamalia Fikri (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This study aims to determine the effect of metacognitive awareness among high school students in using the Inquiry learning model with the help of the Pictorial Riddle. This study used a quasiexperimental study involving students of class XI IPA as an experimental group and a control group. The experimental group applied the Inquiry learning model assisted by the Pictorial Riddle, while the control group applied the STAD learning model with information discussion by forming a small group. Kolmogorov Smirnov's one-sample test and homogeneity were used to select the experimental group and the control group. In this study the measurement of students' metacognitive awareness used the MAI (Metacognitive Awareness Inventory) questionnaire. The number of questions consists of 37 items, of which the questions are divided into three factors which are included in the knowledge of awareness, and five other factors related to the regulation of awareness. The data on the value of metacognition awareness used to measure student’s metacognition awareness were obtained from the MAI questionnaire given to students, both the experimental class and the control class before and after the study, the data obtained were analyzed using the ANAKOVA test, the result show that the model is corrected for the score after MAI treatment, the probability value is 0,000 which is smaller than 0.05 (p = 0,000 <0.05), which means that H0 is rejected and H1 is accepted and there is a significant effect on the Pictorial Riddle-assisted Inquiry learning model on student metacognition.